2020
DOI: 10.2174/1381612826666200417144530
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticles as a Skin Wound Healing Drug Delivery System: Discoveries and Advances

Abstract: : Chronic wounds are a remarkable cause of morbidity, requiring long-time treatments with significant impact on quality of life and high costs for public health. Although there are a variety of topical skin preparations commercially available, they have several limitations that frequently impair wound healing, such as drug instability, toxicity, limited time of action and ineffective skin permeation. In recent years, researchers have focused on the development of new effective treatments for wound healing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 119 publications
0
25
0
Order By: Relevance
“…Furthermore, SLNs being occlusive in nature have good adhesion and film-forming capacity. Both the properties aid in speedy wound healing due to increased hydration and skin integrity [ 24 ]. A report from our lab earlier established the potential of SLNs as scaffold for attachment of stem cells and as cell differentiation inducers [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SLNs being occlusive in nature have good adhesion and film-forming capacity. Both the properties aid in speedy wound healing due to increased hydration and skin integrity [ 24 ]. A report from our lab earlier established the potential of SLNs as scaffold for attachment of stem cells and as cell differentiation inducers [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using this method, it was possible to figure out that the viscoelastic properties of LNPs are dependent on the level of lipid components ( Souto et al, 2004a , Souto et al, 2004b ). In practice, these results showed that LNP dispersions have sufficient viscosity or fluidity for easy application, and sufficient elasticity to adhere onto the skin ( Garcês et al, 2018 , de Souza et al, 2020 ). One of the purposes of cosmetic and toiletry products is to diminish the desire to grate that may cause skin damage.…”
Section: Cosmeceuticals Characteristics Of Lnpsmentioning
confidence: 94%
“…SLNs and NLCs are also showing promise to promote skin regeneration [ 75 , 76 , 77 ]. Recent investigations focused on DTD of essential oils having healing effects due to either a dual anti-inflammatory/collagenesis-inducing action of the oil itself [ 78 ], or to a synergic antimicrobial and healing action elicited by combination of the essential oil with specific components in the lipid nanocarrier (e.g., oleic acid) [ 79 ].…”
Section: Overview Of Current Methods For Dermal and Transdermal Drug Deliverymentioning
confidence: 99%